2018
DOI: 10.1308/rcsann.2018.0086
|View full text |Cite
|
Sign up to set email alerts
|

Predicting in-hospital mortality in older general surgical patients

Abstract: Introduction A significant number of emergency general surgical admissions occur in older patients. Clinical decision making in this group is challenging and current risk prediction tools extrapolate data from cohorts of younger patients. This is the first UK study to examine risk factors predicting in-hospital mortality in older acute surgical patients undergoing comprehensive geriatric assessment. Methods This was a prospective study of consecutive patients aged ≥75 years admitted non-electively to general s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A further systematic review of risk assessment in all emergency laparotomy patients found that none of the tools for risk assessment in older patients could provide adequate discrimination of outcomes although APACHE II was generally the best predictor of mortality [ 21 ]. Frailty and other age-related syndromes such as sarcopenia are independent predictors of perioperative mortality [ 22 25 ]. We have shown in this study that patients who are frail often have worse long-term outcomes in terms of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A further systematic review of risk assessment in all emergency laparotomy patients found that none of the tools for risk assessment in older patients could provide adequate discrimination of outcomes although APACHE II was generally the best predictor of mortality [ 21 ]. Frailty and other age-related syndromes such as sarcopenia are independent predictors of perioperative mortality [ 22 25 ]. We have shown in this study that patients who are frail often have worse long-term outcomes in terms of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have emphasized the negative impact of major GI surgery on functional independence [15, 35, 36]; therefore it is not surprising that surgeons in this study were less likely to suggest major surgery with increasing levels of functional impairment. Functional impairment also correlates with physical inactivity, another predictor of poor outcomes in older patients [37].…”
Section: Discussionmentioning
confidence: 88%
“…ADL is a convenient way to assess a person's functional level, even small changes in the ADL functional level are associated with clinically relevant outcomes [14–18] . It has been reported that dependence in activities of daily living was one of the predictors of in-hospital mortality in older general surgical patients [24] . Dependency in ADL have been proved to influence survival in older patients attending the emergency department or being hospital with orthopaedic or trauma conditions [25–29] .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] It has been reported that dependence in activities of daily living was one of the predictors of in-hospital mortality in older general surgical patients. [24] Dependency in ADL have been proved to influence survival in older patients attending the emergency department or being hospital with orthopaedic or trauma conditions. [25][26][27][28][29] Frailty and delay in management are associated with poor surgical outcomes after emergency abdominal surgery in the elderly.…”
Section: Discussionmentioning
confidence: 99%